Metal Nanoparticles for application in Luminescent Solar Concentrators - SETHI, ARUNIMA (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2020)
Rising global temperature calls for innovative ways to deal with the ever-growing energy demand. Luminescent Solar Concentrators (LSC) are low concentration, solar radiation collectors. LSCs have the potential to be used as building-integrated photovoltaics due to their ability to be architecturally integrated into the facade without compromising the aesthetic of the building. They can concentrate both diffuse and direct solar radiation and that is essential for northern latitude countries where 50% of solar radiation can be diffuse. The various energy loss mechanisms in LSC inhibit the device efficiency from reaching its thermodynamic limit. Plasmonic LSC (PLSC) is a novel concept to reduce the escape cone losses and increase the edge power output of an LSC device. A PLSC comprises of metal nanoparticles (MNPs) and fluorophores embedded in an optical waveguide. The plasmonic coupling between the fluorophore and MNP can increase the fluorescence intensity of the fluorophore by increasing its excitation or emission rate or both. In this Ph.D., work is carried out to synthesize MNPs for application in PLSC and to fabricate and test PLSC device in the European climate. Anisotropic MNPs were synthesized to tune the surface plasmon resonance band position to the absorption or emission peak of the fluorophore. A narrow size and shape yield of the MNPs was achieved and the MNPs were transferred into an organic solvent. The MNPs retained their optical properties without aggregation in the host matrix (Silicone encapsulant). Gold core silver shell nanocuboids were used along with Lumogen Red305 dye to fabricate PLSC devices having broadband plasmonic coupling. Transition from fluorescence enhancement to quenching was observed by changing the doping concentration of MNPs in the PLSC. A 1.2 times increase in the power conversion efficiency was observed for optimized PLSC device as compared to an LSC without any MNPs. PLSC device was studied in different lighting conditions outdoors and higher efficiency than bare PV cell was observed in diffuse radiation. As compared to July, the PLSC device performs 45% better than the PV cell in December. This shows the feasibility of PLSC device in winter months.
APPROVED
Keywords: Luminescent solar concentrators; Surface plasmonic resonance; Solar energy; Metal nanoparticles